Предмет:
МатематикаАвтор:
анонимa) (7 * d - 2)² = (7 * d - 2) * (7 * d - 2) = 49 * d2 - 14 * d - 14 * d + 4 = 49 * d2 - 28 * d + 4;
б) (2 * t + 5 * r)² = (2 * t + 5 * r) * (2 * t + 5 * r) = 4 * t2 + 10 * r * t + 10 * r * t + 25 * r2 = 4 * t2 + 20 * r * t + 25 * r2;
В) -40 * q * s + (4 * q + 5 * s)² = -40 * q * s + 16 * q2 + 40 * q * s + 5 * s² = 16 * q2 + 5 * s²;
Г) 49 * y² - (3 - 7 * y)² = 49 * y² - (9 - 42 * у + 49 * y²) = 49 * y² - 9 + 42 * у - 49 * y² = -9 + 42 * у;
Д) -3 * (3 * a - 5)² = -3 * (9 * a² - 30 * а + 25) = -27 * a² + 90 * а - 75.
Автор:
cheyennecujhДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть